1979
DOI: 10.1021/ja00515a007
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular electron transfer from pentacyanoferrate(II) to pentaamminecobalt(III) mediated by various 4,4'-bipyridines

Abstract: The reactions of Fe(CN)50Hz3-with Co(NH3)sL3+ ( L = bis(4-pyridyl)methane, bis(4-pyridyl)ethane, bis(4-pyridyl)propane, bis(4-pyridyl)ethylene, and bis(4-pyridyl) ketone) produce binuclear complexes (NC)5Fe'1LCo1'1(NH3)s that exhibit iron t2g to ligand K* charge transfer bands at (same order) 370, 365, 360, 500, and 555 nm. Comparison of these values with those for the corresponding Fei1(CN)sL3-complexes (370, 365, 360, 460, and 520 nm) suggests that the electron-withdrawing effect of the Co(ll1) moiety attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…The absorption maxima (t2, + LT* metal-to-ligand charge transfer (MLCT) band) and molar absorptivity coefficients (Table 1) for a number of the complexes in this study have been reported previously (9,12,19,20). The shift in A , , ,…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The absorption maxima (t2, + LT* metal-to-ligand charge transfer (MLCT) band) and molar absorptivity coefficients (Table 1) for a number of the complexes in this study have been reported previously (9,12,19,20). The shift in A , , ,…”
Section: Resultssupporting
confidence: 58%
“…A fit of the data to eq. [9] yielded pK3 values of 3.6 5 0.1 for (H)CH3BPY2+, 4.6 + 0.2 for (H)CH,BPE2+, and 5.6 + 0.1 for (H)CH3BPA2+. The differences between pK3 and pK1 (H,L~+) for the three species are found to be in the range of 0.1-0.3.…”
Section: Kinetic Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…[9,10] The inclusion into the CD cavity also prevents folding of the bpe or bpp units as well as a closed conformation for 5 and 6, as was proposed for [(CN) 5 Fe(bpe)Co(NH 3 ) 5 ]. [11] This excludes any probability of electron transfer ªthrough spaceº because in the absence of folding the two metal centers cannot come closer than 11 which is too large a distance for direct electron transfer through space. Moreover, cyclodextrin is made of carbohydrates and is not expected to mediate electron transfer.…”
mentioning
confidence: 99%